Instagram Dan Twitter Sebagai Strategi Humas Pt Jasa Marga (Persero) Tbk Dalam Meningkatkan Pelayanan - Ningrum, Fitriana Kusuma; Syarah, Maya May (Universitas Ibn Khaldun Bogor, 2018)
The Highway infrastructure that is used for daily mobility for the people of Indonesia. The purpose of the building of highways, one parse congestion. But this time the vehicle's volume growth is inevitable and lead to the emergence of the problem of congestion on the highways. When the highway claim as a freeway. Such a State is certainly is not expected by the toll road users in General. With the information from officials, will greatly assist users in monitoring the State of the highways before using it. Research on this issue is made at PT Jasa Marga, which is the largest Highway management company in Indonesia using qualitative descriptive method. Observation, key informant interviews and additional informants, as well as utilizing previous research is a technique used in drawing up the research. The result of the research shows that strategy by disseminating information